On mediating agents’ moves and how they might affect patient-centredness in mediated medical consultations - Krystallidou, Demi K. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The present study aims to shed some light on indicators that might potentially challenge patient-centredness (as practised by self-professed patient-centred doctors) within a mediated medical encounter, and to contribute to the fields of linguistics, translation studies and medical communication. Selected instances of transcribed video recordings are analysed within the framework of Goffman’s footing and participation roles, while transcribed audio recorded interviews with participants in the triad are taken into consideration as well. Both verbal and non-verbal cues (i.e., gaze) are taken into account. The data is drawn from a corpus of video-recorded mediated consultations in a urban hospital in Belgium. Hospital ethical approval and subjects’ written informed consent have been obtained